Developing Android Based Ambulance Emergency Application in Sleman Region - Gunawan, Gunawan; Itje Sela, Enny; Sri Utami, Wahyu (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
The population of Sleman Regency is 1,318,086 and the death rate is very high. This study searches for people who have difficulty finding ambulance assistance. That’s why an application was created to help sick people arrive on the scene. This app is equipped with LBS (Location-Based Services). This app also uses Firebase as data, a form of Google providing various data services to develop mobile apps like this one in real-time. This app is created in the Java programming language running in Android Studio. Furthermore, this application connects journalists and medical staff directly without the need for intermediaries or other people. In addition to knowing where the ambulance is when it arrives, the app is designed to overcome the problem of doctors determining routes and searching for hard-to-reach victims in an emergency provided with a mobile phone. This application was created to get an ambulance more comfortably and efficiently. The driver will know the exact location of the incident without having to search the incident. He will also get a lot of information. In addition, this application further accelerates quick evacuation of the injured or sick for quick medical assistance. So, this application is practical to use in critical situations. Current technological developments also include many innovations, so this research aims to help people use today’s developing technology more efficiently.